A new route to prepare nanocomposites based on polyvinyl chloride and MgAl layered double hydroxide intercalated with laurylether phosphate (eXPRESS Polymer Letters, 2009)
The MgAl layered double hydroxide (LDH) with laurylether phosphate was prepared using reconstruction method. Delamilation of the LDH with laurylether phosphate (LDH-PK) in tetrahydrofuran was characterized by AFM (atomic force microscopy), indicating that a large part of the LDH was delaminated into single, double and multi layers. The delaminated LDH-PK suspension was then used with polyvinyl chloride (PVC) to prepare a series of high-LDH-loading nanocomposites. Both the XRD (X-ray diffraction) patterns and TEM (transmission electron microscopy) photographs of the as-prepared PVC/LDH nanocomposites indicated that the LDH nanolayers dispersed uniformly in the PVC matrix. With differential scanning calorimetry (DSC) the glass transition temperatures of PVC phases in the PVC/LDH nanocomposites were measured and a slightly lower value than that of pristine PVC has been observed. Thermogravimetric analysis results show that the presence of LDH enhanced the dehydrochlorination temperature (Tmax1), reduced the maximum degradation rate (Rmax1) and the 5% weight loss temperature, and promoted the char formation of PVC. However, the thermal degradation temperature (Tmax2) and thermal degradation rate (Rmax2) of the dehydrochlorinated PVC were slightly affected by the presence of LDH. The apparent activation energies were calculated by the method of Flynn-Wall-Ozawa in nitrogen at four different heating rates, showing that the nanofiller increased the apparent activation energies by 10–26 kJ/mol when compared with pristine PVC, probably implying that the LDH nanolayers improve the stability of chlorine atom on the PVC chains.